Usutu Virus (Flaviviridae, Orthoflavivirus). Potential Danger and Possibility of Spread on the Territory of the Russian Federation - E. V. Naidenova; K. S. Zakharov; K. D. Blinova; I. G. Shvidenko; A. V. Boiko; S. A. Shcherbakova (Проблемы особо опасных инфекций, 2023)
In recent decades, an increase in the number of cases of detection of the Usutu virus (Usutu, USUV, Orthoflavivirus usutuense) (family Flaviviridae, genus Orthoflavivirus) has caused great concern among medical professionals, including virologists and specialists in infectious diseases, especially since its appearance in Europe, where the pathogen caused mass birds die-off, and annually registered human cases. This review provides information about the structure of the virus and its genetic variants, geographical distribution and features of circulation in Europe and Africa, the methods and principles used to indicate and identify this pathogen, as well as the main symptoms of the disease it causes. An assessment of the environmental prerequisites for the occurrence of outbreaks of the disease caused by the Usutu virus on the territory of the Russian Federation was also carried out.